Synthesis and characterization of rough electrochromic phosphotungstic acid films obtained by spray-gel process - Medina, A. (2003)
Rough electrochromic phosphotungstic acid (PWA) films were fabricated by spraying a gel of phosphotungstate anions with a molar ratio of P:W = 1:12 onto glass substrates precoated with transparent and electrically conducting SnO2:F at 300 °C. The analysis by X-ray photoelectron spectroscopy (XPS) determined that the P:W molar ratio in the films was approximately 1:14. Infrared spectroscopy (IR) and X-ray diffraction (XRD) showed that the film is a polycrystalline phosphotungstic acid. SEM micrographs showed that the films present a rough morphology based on fiber-shape bridges. Optoelectrochemical measurements demonstrated pronounced electrochromism in the PWA films upon H+ intercalation/deintercalation with a high diffuse reflectance (Rd) and transmittance (Td). We found for as-deposited films that Rd/total reflectance (Rt) and Td/total transmittance (Tt) at 550 nm was around 0.83 and 0.68, respectively. This ratio decreases at bleached state to 0.74 and 0.41 for Rd/Rt and Td/Tt, respectively.